PROBLEMS AND SOLUTIONS FOR TEACHING GRAPHIC SUBJECTS ONLINE - Jurane, Ieva; Leja, Ella (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Due to the COVID-19 pandemic, schools and universities around the world are moving to online learning. Various technologies and techniques have been invented around the world, but they do not solve simple problems such as task logistics between teacher and student. There is a large non-creative additional work load. The article discusses the problems encountered in teaching graphic subjects online and the tools and techniques that can be used.Breakout rooms in ZOOM have been found as a good option for practical work in engineering graphics. The aim of the article is to describe the experience gained in teaching engineering graphics online in the spring and autumn semesters of 2020, as well as to analyse the results of the survey at the end of the year.